Burnout, percepção de suporte social e autoeficácia em estudantes do Ensino Superior - Ramos, Daniela Aparecida de Sousa Moreira (2015)
Student burnout is a process evidenced by the physical and mental exhaustion meet the demands of the study, by cynical attitude and behavior of detachment for the academic context, by feelings of ineffectiveness and incompetence with regard to student. Due the lack of national studies on burnout in university students and its importance in current and professional life of the public, this study investigated the influence of demographic variables (gender, age, sports practice and period of the course), the perception of social support and self-efficacy beliefs in higher education in the development of burnout. The sample, for convenience, constituted by 274 university students with a mean age of 23 years (SD = 5.61), mostly female, single and living with family. Most students enrolled for less than two years at the institution and were still in the basic training periods (first thirty months of the course). Trustworthy and reliable instruments for data collection were used, analyzed using descriptive statistics, reliability of scales and standard multiple regression, having the dimensions of burnout as variable-criterion. The reliability of scales for the sample was above 0.70. Among the results, it was observed that the sample is at risk of developing burnout considering the moderate scores on emotional exhaustion, first to appear as burnout development model. Still it was found that age, period of the course, gender and academic self-efficacy explained 11% of the variance in dimension emotional exhaustion; period of the course and academic management self-efficacy also influenced 20% of the variance of cynical attitudes and distancing behaviors of students and, finally, the period of the course and academic self-efficacy contributed 39% of variance of feelings of competence and personal student achievement. The dimensions of perceived social support did not explain the development of burnout in this sample. The conclusion of the study points out the importance of age, period of the course and self-efficacy beliefs in higher education with regard to the development of burnout, suggesting the need for programs that support actions that help students both in entry and in completion of the course, aiming at the prevention of burnout and promoting quality of life in the university context, thus contributing to the training of students. It is recommended to carry out studies covering new samples, as well as research of other variables that may mediate and influence the development of burnout in the higher education context.